Book Review: Arjun Guneratne and Anita M. Weiss (eds), Pathways to Power: The Domestic Politics of South Asia. (June 2016) - Schneider, Mark
Arjun Guneratne and Anita M. Weiss (eds), Pathways to Power: The Domestic Politics of South Asia. New Delhi: Orient Blackswan. 2014. 420 pages. ₹ 1, 070.